RANCANGAN APLIKASI SISTEM PENGELOLAAN KEUANGAN PRIBADI MENGGUNAKAN METODE KAKEIBO BERBASIS ANDROID - Suharni -; Eel Susilowati; Muhammad Rimbadi Ma'rif (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2023)
ABSTRACT The 2022 National Survey of Financial Literacy and Inclusion (SNLIK) describes a financial literacy index of 49.68% and a financial inclusion index of 85.10%. This value increased compared to the results in 2019.However, that in general the Indonesian people do not understand the use of financial products or services and financial management to achieve prosperity.To overcome the lack of financial literacy, there is a financial method called Kakeibo. Therefore, Create a personal financial management application design using the Android-based Kakeibo method to be a solution in managing personal finances. The application was created using the waterfall method starting from the analysis stage, design, coding ,and testing. At the analysis stage, determine the features that will be created according to the needs of application users. At the design stage, a design is created using the UML (Unified Modeling Language) model which consists of use case diagram, activity diagram, class diagram, and interface design in accordance with the features that have been determined at the analysis stage. The design model and features created describe how users interact with Personal financial management information system application using Kakeibo based on Android mobile. The application design has been successfully created, The next stage can be implemented by coding according to the program design and testing. Keyword : Application, Financial Management, Kakeibo, Android